The combination of rAAV pseudo-lipid nanoparticle and triamcinolone acetonide enables multi-administration to liver - Chunmei Gan; Mi Leng; Yu Liu; Zhaoyue Zheng; Siwu He; Wen Qiao; Lin Xiao; Yao Xiao; Jingya Ye; Lixing Zhou; Jiao Zhou; Boduan Xiao; et al. (Molecular Therapy: Methods & Clinical Development)
The multi-administration of recombinant adeno-associated virus (rAAV) is limited largely by immunological barriers. Herein, a novel strategy, named rAAV pseudo-lipid nanoparticle combined with triamcinolone acetonide (LNP-rAAV + TAC), has been described in mice. We showed successful but low efficient triple trafficking by LNP-rAAV2 carrying EGFP, human factor IX (hFIX), and luciferase (luc), due to its encapsulation characteristic. Additionally, sustained TAC treatment, which dose-dependently downregulated the anti-rAAV2 antibodies, permitted rAAV2 re-administration at dosages of ≥45 mg/kg/3 days. Furthermore, to improve the efficiency and safety, LNP-rAAV + TAC was evaluated, using LNP-rAAV2 carrying EGFP, hFIX, and luc co-treating with 45 mg/kg/3 days TAC before and after treatment with LNP-rAAV2 injections. Notable neutralizing antibody reductions of 37.8-fold and 12.7-fold were observed by the combinatorial strategy compared with the independent LNP encapsulation and TAC treatment approaches. The plasma hFIX protein was enhanced to 15.1 μg/mL and the liver bioluminescence was elevated to 1.4 × 108 p/s/cm2/sr following the second and third administrations, with weaker levels in LNP encapsulation (1.9 μg/mL, 2.1 × 104 p/s/cm2/sr) and TAC treatment (3.0 μg/mL, 6.1 × 104 p/s/cm2/sr) groups. Thus, this combination strategy is an attractive candidate for enabling multi-dosing of rAAV vector and warrants further study on the underlying mechanism.